Comparison of buckwheat genomes reveals the genetic basis of metabolomic divergence and ecotype differentiation - He, Ming; He, Yuqi; Zhang, Kaixuan; Lu, Xiang; Zhang, Xuemei; Gao, Bin; Fan, Yu; Zhao, Hui; Jha, Rintu; Huda, Md Nurul; Tang, Yu; Wang, Junzhen; et al. (Wiley, 2022)
Golden buckwheat (Fagopyrum dibotrys or Fagopyrum cymosum) and Tartary buckwheat (Fagopyrum tataricum) belong to the Polygonaceae and the Fagopyrum genus is rich in flavonoids. Golden buckwheat is a wild relative of Tartary buckwheat, yet golden buckwheat is a traditional Chinese herbal medicine and Tartary buckwheat is a food crop. The genetic basis of adaptive divergence between these two buckwheats is poorly understood. Here, we assembled a high‐quality chromosome‐level genome of golden buckwheat and found a one‐to‐one syntenic relationship with the chromosomes of Tartary buckwheat. Two large inversions were identified that differentiate golden buckwheat and Tartary buckwheat. Metabolomic and genetic comparisons of golden buckwheat and Tartary buckwheat indicate an amplified copy number of FdCHI, FdF3H, FdDFR, and FdLAR gene families in golden buckwheat, and a parallel increase in medicinal flavonoid content. Resequencing of 34 wild golden buckwheat accessions across the two morphologically distinct ecotypes identified candidate genes, including FdMYB44 and FdCRF4, putatively involved in flavonoid accumulation and differentiation of plant architecture, respectively. Our comparative genomic study provides abundant genomic resources of genomic divergent variation to improve buckwheat with excellent nutritional and medicinal value.Golden buckwheat (Fagopyrum dibotrys or Fagopyrum cymosum) and Tartary buckwheat (Fagopyrum tataricum) belong to the Polygonaceae and the Fagopyrum genus is rich in flavonoids. Golden buckwheat is a wild relative of Tartary buckwheat, yet golden buckwheat is a traditional Chinese herbal medicine and Tartary buckwheat is a food crop. The genetic basis of adaptive divergence between these two buckwheats is poorly understood.Here, we assembled a high‐quality chromosome‐level genome of golden buckwheat and found a one‐to‐one syntenic relationship with the chromosomes of Tartary buckwheat. Two large inversions were identified that differentiate golden buckwheat and Tartary buckwheat.Metabolomic and genetic comparisons of golden buckwheat and Tartary buckwheat indicate an amplified copy number of FdCHI, FdF3H, FdDFR, and FdLAR gene families in golden buckwheat, and a parallel increase in medicinal flavonoid content. Resequencing of 34 wild golden buckwheat accessions across the two morphologically distinct ecotypes identified candidate genes, including FdMYB44 and FdCRF4, putatively involved in flavonoid accumulation and differentiation of plant architecture, respectively.Our comparative genomic study provides abundant genomic resources of genomic divergent variation to improve buckwheat with excellent nutritional and medicinal value.